Combining OCT and OCTA for focal structure-function modeling in early primary open-angle glaucoma - Wong, Damon (2022)
PURPOSE. To investigate modeling of the focal visual field (VF) loss by combining structural measurements and vascular measurements in eyes with early primary open-angle glaucoma (POAG). METHODS. In this cross-sectional study, subjects with early glaucoma (VF mean deviation, ≥−6 dB) underwent optical coherence tomography (OCT) imaging, optical coherence tomography angiography (OCTA) imaging, and Humphrey 24-2 VF tests. Capillary perfusion densities (CPDs) were calculated after the removal of large vessels in the OCTA images. Focal associations between VF losses at the individual VF test locations, circumpapillary retinal nerve fiber layer (RNFL) thickness measurements from OCT, and CPDs were determined using nerve fiber trajectory tracings. Linear mixed models were used to model focal VF losses at each VF test location. RESULTS. Ninety-seven eyes with early POAG (VF mean deviation, −2.47 ± 1.64 dB) of 71 subjects were included. Focal VF modeling using a combined RNFL-CPD approach resulted in a median adjusted R2 value of 0.30 (interquartile range [IQR], 0.13-0.55), whereas the RNFL-only and CPD-only approaches resulted in median values of 0.22 (IQR, 0.10-0.51) and 0.26 (IQR, 0.10-0.52), respectively. Seventeen VF locations with the combined approach had an adjusted R2 value greater than 0.50. Likelihood testing at each VF test location showed that the combined approach performed significantly better at the superior nasal VF regions of the eyes compared with the univariate approaches. CONCLUSIONS. Modeling of focal VF losses showed improvements when structural thickness and vascular parameters were included in tandem. Evaluation of VF defects in early glaucoma may benefit from considering both RNFL and OCTA characteristics.